Blood Factor XI after Fat-Rich Meals - Egeberg, O (Thrombosis and Haemostasis, 1966)
Controlled meals were given to normal persons and to certain patients, and blood coagulation was investigated before and after the meal, especially with an assay sensitive for activated antihemophilic C factor (AHC5 = activated f. XI).After bread and rich amounts of margarine (produced mainly from hydrogenated marine oils), the AHC’ assay in fresh plasma registered a significant acceleration about 5 hours after the meal. No significant changes were measured in the levels of AHA (f. VIII), AHB (f. IX) and proconvertin (f. VII). A weaker tendency to acceleration in AHC5 assay seemed also to occur after intake of vegetable margarine (produced from hydrogenated vegetable oils). Bread with low or high amounts of cow butter gave no acceleration.The active principle in the postprandial plasmas could not be demonstrated after a few days of storage at — 20° C.The hypothesis that the acceleration effect is due to an activation of blood AHC was supported by the observation that no corresponding effect was measured after margarine meals to patients with AHC deficiency.Patients with von Willebrand’s disease showed the same activation as normals.The activation seemed to be prevented by intake of linseed oil prior to the margarine meal.The results are discussed.